2016
DOI: 10.1002/stem.2413
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Factors Control the Fate of Melanoma Tumor Initiating Cells

Abstract: Melanoma is a highly heterogeneous tumor for which recent evidence supports a model of dynamic stemness. Melanoma cells might temporally acquire tumor-initiating properties or switch from a status of tumor-initiating cells (TICs) to a more differentiated one depending on the tumor context. However, factors driving these functional changes are still unknown. We focused on the role of cyto/chemokines in shaping TICs isolated directly from tumor specimens of two melanoma patients, namely Me14346S and Me15888S. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 56 publications
(61 reference statements)
0
18
0
1
Order By: Relevance
“…Immune suppressive factors in the tumor microenvironment TME have also been suggested as pathways of resistance. Tumor-derived immunosuppressive cytokines, like IL-10 and exosomes, have been noted [95,96] . These observations will lead to novel combinatorial therapies directed at these pathways.…”
Section: Immunosuppressive Tumor Microenvironmentmentioning
confidence: 99%
“…Immune suppressive factors in the tumor microenvironment TME have also been suggested as pathways of resistance. Tumor-derived immunosuppressive cytokines, like IL-10 and exosomes, have been noted [95,96] . These observations will lead to novel combinatorial therapies directed at these pathways.…”
Section: Immunosuppressive Tumor Microenvironmentmentioning
confidence: 99%
“…13 Indeed, anti-CTLA4 monoclonal antibodies, ipilimumab and tremelimumab have shown promise in clinical trials 11,14 in patients with metastatic melanoma. Tuccito et al 15 were able to demonstrate another effective means to modifying the immunologic tumor microenvironment. They demonstrated that interleukin-6 (an inflammatory cytokine) released from differentiated melanoma cells reduced MSC self-renewal and instead induced differentiation.…”
Section: Melanoma Stem Cellsmentioning
confidence: 99%
“…By silencing interluekin-10 by blocking the IL-10 receptor. Tuccito et al 15 were able to sensitize MSCs to interleukin-6 and thus induce MSC differentiation. Through these cytokine manipulations, they were able to decrease MSC self-renewal capacity, and instead differentiate stem cells to a more easily targeted phenotype.…”
Section: Melanoma Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…обладающих бесконечным пролиферативным потенциалом, но не обладающих низкодифференцированным фенотипом, in vivo стволовые раковые клетки могут возникать de novo, давая начало опухоли. Такая модель «динамической стволовости» показана, в частности, для меланом, клетки которых могут временно приобретать «рак-инициирующие» свойства, а также переходить из состояния «инициирующих клеток» в более дифференцированное в зависимости от опухолевого контекста [22]. В других работах также была показана возможность перехода раковых клеток в обоих направлениях от клеток с признаками стволовых клеток к дифференцированным клеткам и обратно [23,24].…”
Section: Introductionunclassified